2019
DOI: 10.1038/s41598-019-41731-y
|View full text |Cite
|
Sign up to set email alerts
|

The formin Drosophila homologue of Diaphanous2 (Diaph2) controls microtubule dynamics in colorectal cancer cells independent of its FH2-domain

Abstract: In this study, we analyzed the functional role of the formin Drosophila Homologue of Diaphanous2 (Diaph2) in colorectal cancer cells. We show that stable down-regulation of Diaph2 expression in HT29 cells decreased chromosome alignment and the velocity of chromosome movement during M-phase, thus reducing the proliferation rate and colony formation. In interphase cells, Diaph2 was diffusely distributed in the cytosol, while in metaphase cells the protein was located to spindle microtubules (MTs). Diaph2-depleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…5a), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization [35][36][37]. When re-analyzing normalized RNA-seq data generated by Cho et al, retrieved from GEOrepository (GSE111582), both, DIAPH2 and HOXD10, showed lower expression in RDEB-cSCC versus RDEB-skin tissue [8], ( Supplementary Fig.…”
Section: Diaph2 Is Deregulated In Rdeb-cscc and Predicted To Be A Tarmentioning
confidence: 95%
“…5a), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization [35][36][37]. When re-analyzing normalized RNA-seq data generated by Cho et al, retrieved from GEOrepository (GSE111582), both, DIAPH2 and HOXD10, showed lower expression in RDEB-cSCC versus RDEB-skin tissue [8], ( Supplementary Fig.…”
Section: Diaph2 Is Deregulated In Rdeb-cscc and Predicted To Be A Tarmentioning
confidence: 95%
“…We nominated diaphanous related formin 2 ( DIAPH2) for further evaluation based on significant differences in Kaplan Meier survival curves (p < 0.05, log-rank test, Figure 5A), together with the fact that it was listed as a putative target of miR-10b. Its potential disease-relevance was substantiated by its recent association with colon carcinoma, and its potential role in actin-organization and microtubule stabilization (35-37). When re-analyzing normalized RNA-seq data generated by Cho et al , retrieved from GEO-repository (GSE111582), both, DIAPH2 and HOXD10 , showed lower expression in RDEB-SCC versus RDEB-skin tissue (8, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although formin family proteins are known as actin polymerization promoters highly conserved in eukaryotes, its microtubule-related functions have also been reported [ 22 , 23 , 24 , 25 , 26 ]. For example, Daam and Inf2 are involved in microtubule acetylation, and Diaph2 , an isoform of Diaph3 , is involved in microtubule dynamics [ 25 , 27 ]. To test whether Diaph3 also has microtubule-related functions, we focused on acetylated α-tubulin, a sign of stabilized microtubules, and observed its level.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, based on the results of multinucleation analysis using the mutant DIAPH3 ( Figure 5 B), it is likely that I704 and I733 are involved in the destabilization of the microtubule. On the other hand, DIAPH2 has been reported to be involved in microtubule dynamics without the FH2 domain [ 27 ], and it is possible that DIAPH3 possesses functional domains for microtubule regulation other than the FH2 domain. The analysis of DIAPH3 domains by using deletion mutants will help elucidate the function of Diaph3 in cytokinesis.…”
Section: Discussionmentioning
confidence: 99%